A contextual approach to women's entrepreneurship in Latin America: impacting research and public policy. (17th March 2021) - Ruiz-Martínez, Rocío; Kuschel, Katherina; Pastor, Inmaculada
The field of 'women in entrepreneurship' is growing attention from public policy and academia. However, the literature has been dominated by models and frameworks that were developed mostly in developed economies with a set of particular characteristics that do not match the Latin American reality. This conceptual paper identifies five contextual conditions to consider while analysing women's entrepreneurship in Latin America compared to the Northern Hemisphere: 1) high rates of women's entrepreneurship; 2) high rates of informality; 3) traditional culture and self-expression; 4) low rates of innovation-based ventures; 5) developing ecosystems. We discuss how these contextual conditions interact with the COVID-19 pandemic and economic crisis. Finally, both a research agenda and a public agenda are suggested. This article calls for a Latin American research perspective on women entrepreneurs and suggests that promoting women into sustainable entrepreneurship contributes to regional development, impacts economic activity, improves income distribution, reduces poverty and fosters gender equality.